The Intergenerational Transmission of Chronic Pain from Parents to Survivors of Childhood Cancer - Michaela Patton; Mehak Stokoe; Caitlin Forbes; Chidera Nwaroh; Melanie Noel; Kathleen Reynolds; Fiona Schulte (MDPI AG, 2020)
Background: Among youth with chronic non-cancer pain, 50% have parents with chronic pain. These youth report significantly more pain interference and posttraumatic stress symptoms (PTSS), and worse health-related quality of life (HRQL) than youth whose parents do not have chronic pain. Additionally, parent chronic pain is linked to increased child anxiety and depressive symptoms. Survivors of childhood cancer (SCCs) are at risk of pain and negative psychosocial outcomes and therefore may be especially vulnerable if their parents have chronic pain. Thus, the aims of the current study were to (1) identify rates of chronic pain among parents of SCCs, (2) test group differences in psychological symptoms in parents with chronic pain versus without, and (3) test group differences in pain interference, HRQL, anxiety, depression, and PTSS in SCCs with parents with chronic pain versus without. Methods: 122 SCCs (Mean age = 15.8, SD = 4.8, 45.7% male, Mean age at diagnosis = 5.9, SD = 4.7) and their parents were recruited from across Canada to complete online questionnaires. Parents were asked if they have had pain for at least three consecutive months and completed the brief symptom inventory (BSI) as a measure of psychological symptomatology. Survivors completed the pain questionnaire, patient reported outcomes measurement information system (PROMIS)-pain interference, anxiety, and depression measures, child posttraumatic stress scale, posttraumatic stress disorder checklist for the Diagnostic and Statistical Manual of Mental Disorders, and the pediatric quality of life inventory. Results: Forty-three (39%) parents of SCCs reported having chronic pain. Of the 29 survivors who had chronic pain, 14 (48%) also had parents with chronic pain. Parents with chronic pain reported significantly higher scores on the BSI than parents without chronic pain, F(1, 116) = 5.07, p = 0.026. SCCs with parents with versus without chronic pain reported significantly higher PTSS F(1, 105) = 10.53, p = 0.002 and depressive symptoms F(1, 102) = 6.68, p = 0.011. No significant differences were found across the other variables tested. Conclusions: Findings suggest that survivors' parents' own pain is prevalent and is related to survivors' increased depressive symptoms and PTSS, but not anxiety, pain interference, or HRQL. Future research should explore whether parents may benefit from psychological intervention after their child has been diagnosed with cancer and how this could improve outcomes for their child.